Program Pengenalan Jurusan Teknik Melalui Aktivitas Fun Science Experiment Bagi Siswa MTS Darul Hikmah - RYANU, HARFAN HIAN; Pramudita, Aloysius Adya; Sudjai, Miftadi (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2023)
Madrasah Tsanawiyah (MTS) is a formal education provider at the junior high school level with more emphasis on the content of Islamic Religious Education. MTS students generally have low exposure to the world of science and engineering so that very few/rare madrasah students continue their education, especially lectures in Engineering majors. This community service activity with the title "Introduction to the Engineering Department through Fun Science Experiment Activities for MTS Darul Hikmah Students" aims to increase students' interest from an early age in the world of science and engineering. The method used is project-based learning where students are involved in activities to design fans and automatic floor cleaners using batteries and a simple microcontroller. A total of 22 students from grade 7 at MTS Darul Hikmah were involved in this activity.This activity received a positive response from the target community. As many as 100% of participants were very satisfied with the output of the activity, and 100% of participants considered the activity very useful. As many as 90.5% of participants rated the activities as helping to provide aspirations for future goals, while as many as 9.5% of participants considered the activities unhelpful. In addition, 85.7% felt that this activity encouraged students to learn more about science and engineering, while 14.3% felt that the activity had no impact. That way, this activity can be concluded to have the output according to the expected target.